2022
DOI: 10.1002/pros.24299
|View full text |Cite
|
Sign up to set email alerts
|

Plasma IL‐6 and TNF‐α levels correlate significantly with grading changes in localized prostate cancer

Abstract: Purpose To study the effect of inflammatory markers in blood such as interleukin‐6 (IL‐6) and tumor necrosis factor‐alpha (TNF‐α) on the Gleason score (GS) changes in patients with prostate cancer (PCa) after radical prostatectomy (RP), we conducted this study. Patients and methods From November 2012 to September 2021, a total of 237 patients underwent RP at our institution. Blood samples from all patients were collected within 1 week before surgery. Preoperative clinical characteristics include age, serum IL‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In a study performed on 74 PCa patients, Nakashima et al [47] found that serum IL-6 significantly correlated with the clinical stage of PCa, as recently confirmed by Zhou et al [48] in a study showing that plasma IL-6 and TNFα levels significantly correlate with grading changes in localized PCa. IL-6R signaling has been demonstrated to be crucial in favoring the neuroendocrine differentiation in PCa, by the canonical activation of STAT3 transcription factor (Figure 1B) [49].…”
Section: Il-6mentioning
confidence: 71%
“…In a study performed on 74 PCa patients, Nakashima et al [47] found that serum IL-6 significantly correlated with the clinical stage of PCa, as recently confirmed by Zhou et al [48] in a study showing that plasma IL-6 and TNFα levels significantly correlate with grading changes in localized PCa. IL-6R signaling has been demonstrated to be crucial in favoring the neuroendocrine differentiation in PCa, by the canonical activation of STAT3 transcription factor (Figure 1B) [49].…”
Section: Il-6mentioning
confidence: 71%
“…Independent predictors of pathology grade upgrading identified in different studies may be listed as non-white race, older age, higher PSA levels, cancer positive biopsy fraction, prostate volume, prostate density and tumor percentage of >50% per core [18][19][20][21][22][23]. In a recent study, cancer upgrade has been shown to have a positive correlation with increased levels of TNF-alpha and a negative correlation with high levels of IL-6 (24). In an article by Epstein al., GS upgrading from <6 to a higher grade happened in 36.3% of 7643 cases [4].…”
Section: Discussionmentioning
confidence: 99%
“…In these mice, the FSMP diet significantly increased overall survival ( p < 0.01), delayed progression from prostatic intraepithelial neoplasia to adenocarcinoma, and decreased the incidence of poorly differentiated cancer. Biochemical studies disclosed a decrease in antioxidant activity in animal sera and a reduction in the circulating biomarkers of relevance to prostate carcinogenesis, such as IL-6 and TNF-α, which significantly correlated with PCa grade [ 116 ] and VEGF, known to be associated with prostate tumor grade, metastasis, and prognosis [ 117 ]. Indeed, the IL-6/STAT axis represents a link between inflammation and prostate carcinogenesis [ 105 ], which is the signal transducer and activator of transcription 3 (STAT3), a key modulator in the expression of a wide range of oncogenic genes [ 118 ] and a player in prostate cancer energy [ 119 ].…”
Section: Tomato and Olive Oil In Prostate Healthmentioning
confidence: 99%